2020
DOI: 10.1111/gfs.12468
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selection methods among and within full‐sibling progenies in Urochloa humidicola

Abstract: Hybridization in the Urochloa humidicola breeding programme allowed to explore the genetic variability of the apomictic sources and, thus, to obtain new sexual and apomictic parents with compatible ploidy and/or superior progenies. However, given the high variability arising from crosses, there is a need to adopt efficient selection strategies among and within progenies. The aim of this study was to compare the selection methods among U. humidicola progenies with (t‐BLUP) and without (BLUP) the weighting based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Hence, forage breeding programs could benefit from allocating resources to fewer genotypes in the following generations. Nevertheless, in both cases (selecting versus discarding), it is important to consider that perennial grass breeding programs have a peculiar regrowth evaluation (Berchembrock et al 2020), which limits the number of generations and selection cycles on a per year basis. Various forage breeding programs have used visual evaluation to assess traits at different stages of selection cycles for crops such as red clover (Riday 2009), U. ruziziensis (Souza Sobrinho et al 2010, Teixeira et al 2020, U. decumbens (Matias et al 2020), U. humidicola (Figueiredo et al 2019), and Urochloa spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, forage breeding programs could benefit from allocating resources to fewer genotypes in the following generations. Nevertheless, in both cases (selecting versus discarding), it is important to consider that perennial grass breeding programs have a peculiar regrowth evaluation (Berchembrock et al 2020), which limits the number of generations and selection cycles on a per year basis. Various forage breeding programs have used visual evaluation to assess traits at different stages of selection cycles for crops such as red clover (Riday 2009), U. ruziziensis (Souza Sobrinho et al 2010, Teixeira et al 2020, U. decumbens (Matias et al 2020), U. humidicola (Figueiredo et al 2019), and Urochloa spp.…”
Section: Discussionmentioning
confidence: 99%
“…Some agronomic traits in U. ruziziensis and other forages are often visually assessed under field conditions because this assessment is practical and effective. Traits routinely evaluated using such techniques include i) pest and disease resistance (Silva et al 2013), ii) regrowth capacity (Berchembrock et al 2020, iii) stay-green (Wilkinson and Hill 2003), and iv) plant growth and biomass production (Burton 1982, Price andCasler 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that genitors selected using PCA Biplot were similar to multivariate indices, thus proving to be an excellent visual tool to apply selection for multi-traits. Efficient selection strategies among and within progenies were evaluated in U. humidicola (Berchembrock, de Figueiredo, Nunes, do Valle, & Barrios, 2020), where selection based on Studentized best linear unbiased prediction (t-BLUP) proved to be more advantageous regarding the use of best linear unbiased prediction (BLUP) not weighted resulting in higher selection gains.…”
Section: Crop Sciencementioning
confidence: 99%
“…During evaluation, characteristics related to persistence and productivity are generally major traits of interest (Figueiredo et al., 2019). Testing novel materials against industry standards such as Marandu palisadegrass and Basilisk signalgrass may expedite release of improved cultivars that fulfill specific industry needs in addition to achieving greater pasture diversification (Berchembrock et al., 2020).…”
Section: Introductionmentioning
confidence: 99%